STRATEGI PENDIDIK DALAM MENUMBUHKAN KARAKTER DISIPLIN PADA ANAK USIA DINI - Afida, Nurul; Kholis, Mohd (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2023)
Disciplinary character education should be instilled from an early age, the assumption that early childhood discipline does not need to be implanted because it is too young is a misconception. Character is an attitude or habit that is inherent in a child until the child becomes an adult. Man is a unidualistic creature, that is, man as an individual and social being. The application of discipline to the child aims to enable the child to play a role as a social being because it is in conflict with the individual life and social life of the child, therefore the child must be trained and disciplined in order to be able to adapt to the social life. Children can shape their behavior according to the role given by the cultural group with which the individual is identified. Since there is no uniform cultural model, friction with the social environment is inevitable, so that the child can enter the social setting requires a character that is acceptable to the social surroundings.